Increasing Sales Volume using Social Media Facebook and WhatsApp Features (Case Study on Clothes and Women's Accessories) - Al Sabet, Fia Birtha; Yunita, Ita (ProBisnis : Jurnal Manajemen, 2025)
Social media is actually a medium for socialization and interaction, and attracts other people to see and visit links containing information about products, and can also be used as the easiest and cheapest marketing media. Entrepreneurs from large companies use social media with the aim of finding new markets and maintaining relationships with existing consumers. One of them is done by online shops on Facebook and WhatsApp which are engaged in online business. The target marketing of online shops on Facebook and WhatsApp is young people to adults. Problems that often occur in buying and selling activities on online shops on Facebook and WhatsApp, one of which is that several online shop users on Facebook and WhatsApp who act as sellers, sell goods that do not match the images that have been listed. So what happens is a decrease in consumer trust in online shops on Facebook and WhatsApp, consumers tend to be more careful in shopping, which has an impact on decreasing sales volume in buying and selling on Facebook and WhatsApp. Based on these things, it is necessary to conduct research on increasing sales volume through social media Facebook and WhatsApp. The method used is a qualitative method. Based on the results of the research conducted, it can be concluded that the use of social media Facebook and WhatsApp can increase sales volume and sales activities become more effective in increasing product promotion at a low cost. In addition, with social media Facebook and WhatsApp, the market reach is also wider and easier to access from anywhere and by anyone. However, there are obstacles or barriers that arise due to internet network problems, differences in photo or video results from the devices used, and the potential for fraud from sellers and buyers.